Analisis Faktor-Faktor yang Mempengaruhi Kepuasan Kerja Karyawan terhadap Kesejahteraan Karyawan di PT. Mohtra Agung Persada - Syafitri, Kharisma; Waluyo, Minto (Fakultas Ekonomi Universitas Samudra, 2024)
This research aims to determine the relationship between co-worker relationships, supervision, working conditions and changes in career status on employee satisfaction, as well as knowing the relationship between job satisfaction and employee welfare at PT. Mohtra Agung Persada. The sample for this quantitative research is employees of PT. Mohtra Agung Persada numbered 150 respondents. Data was obtained from distributing questionnaires using a Likert scale, then analyzed using the structural equation modeling (SEM) method. The results of this research found that co-worker relationships and career development were proven to have a positive and significant effect on employee job satisfaction, and supervision and working conditions were proven to have no significant effect on employee job satisfaction. Moreover, the results show that job satisfaction has a positive and significant effect on employee job satisfaction.